The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.4236/ce.2023.1411140
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Pandemic (COVID-19) on Higher Education Students: Challenges, Adaptations, and Future Perspectives

Sarwar Khawaja,
Ester Anjos,
Fayyaz Qureshi

Abstract: In January 2020, the World Health Organization (WHO) declared the outbreak of the novel coronavirus as a Public Health Emergency of International Concern (PHEIC), leading to the implementation of restrictive protective measures. Building on this issue, this article aims to analyse the impact of the COVID-19 pandemic on higher education students, addressing the challenges faced, adaptations made, and future perspectives. To achieve this, the strategies adopted by educational institutions were explored, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
(20 reference statements)
0
0
0
Order By: Relevance
“…Amid the recent pandemic, employees within the HE sector experienced a significant transformation in their digital work landscape [3,4,6]. In response to the closure of physical campuses and the need to adhere to social distancing regulations, institutions swiftly transitioned to remote and online teaching, administrative functions, and student support services [3].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 3 more Smart Citations
“…Amid the recent pandemic, employees within the HE sector experienced a significant transformation in their digital work landscape [3,4,6]. In response to the closure of physical campuses and the need to adhere to social distancing regulations, institutions swiftly transitioned to remote and online teaching, administrative functions, and student support services [3].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…COVID-19 research has indicated that the abrupt transition to remote work presented numerous obstacles, including work disruptions, socio-economic hardships such as job loss, and adverse effects on mental health, such as stress, anxiety, and feelings of isolation during the pandemic [2][3][4][5][6][7]. Many workers experienced notable changes in their overall digital engagement amid the COVID-19 crisis [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations